(untitled) (Global Journal of Human-Social Science, 2021)
The objective of this article is to learn more about the phenomenon of bilingualism and biculturalism that can be traced in Roman epigraphic manifestations, taking as an object of study the monument known as Ara del Sol Sanctissimus, created by the Palmyrene community living in Rome. To achieve our task we will refer, first, to some of the most significant characteristics of Roman epigraphy, to the relations between Rome and Palmyra and, finally, we will address the study of the components of the document that we are interested in analyzing on this occasion. In this way, the importance that epigraphic sources cover in our knowledge of some aspects related to the ancient Roman world will be shown.